2001
DOI: 10.1097/00132580-200109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Myocardial Apoptosis as a Therapeutic Target in Cardiovascular Disease Prevention

Abstract: Apoptosis is a type of programmed cell death that is evident during embryonic development and normal tissue turnover. When the apoptotic activity extends beyond physiologic limits, it can determine and/or contribute to those pathologic states characterized by excessive cell loss and impairment of organ function. The clinical development of caspase inhibitors may represent a potential therapeutic strategy for influencing the onset and progression of ventricular dysfunction to terminal failure. This article focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…It has been shown that caspase-3 expression is increased in association with heart failure and apoptosis in experimental animals. 34 Several groups have reported that direct blockade of caspase activation with a peptide inhibitor protects the myocardium against lethal reperfusion injury. 34,35 In contrast, hearttargeted overexpression of caspase-3 in mice has been shown to increase infarct size and depress cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that caspase-3 expression is increased in association with heart failure and apoptosis in experimental animals. 34 Several groups have reported that direct blockade of caspase activation with a peptide inhibitor protects the myocardium against lethal reperfusion injury. 34,35 In contrast, hearttargeted overexpression of caspase-3 in mice has been shown to increase infarct size and depress cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…poptosis, or programmed cell death, is mediated by the activation of caspases (cysteine-containing aspartatespecific proteases, a group of proteolytic enzymes) and is thought to be a critical component of acute and chronic diseases such as myocardial infarction, stroke, neurodegenerative diseases, and disc degeneration [1][2][3] . There are several caspases, and they act as either initiators (caspase-2, 8, and 9) or executioners (caspase-3, 6, and 7) of apoptosis 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Pancaspase inhibition more effectively decreased apoptosis than did caspase-8 inhibition. The use of caspase inhibitors has been reported to prevent or attenuate cell death associated with ischemic injury in the brain and heart and to protect against hepatic toxicity 1,[8][9][10][11][12][13] . Our results suggest that pancaspase inhibitors might offer a therapeutic benefit in the treatment of disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Continued investigation into pharmacological and catheterbased interventions that preserve myocardial function is needed to amplify the benefits of a pharmacoinvasive strategy. [81][82][83][84] Figure 3. Proposal for pharmacoinvasive reperfusion of patients with STEMI in the future.…”
Section: Antman and Van De Werf Future Of Treatment For St-elevation MImentioning
confidence: 99%